Diagnóstico y mejora del proceso de logística de la empresa Envases Gemelos Perú S. A. C. - Esteves Rodriguez, Diego Alonso (2023)
In the following summary, the diagnosis and improvement in the logistics process of a trading company of bags and laminates based on polypropylene is shown. The objective of the project is to establish alternative solutions that help reduce losses due to non-compliance with certain orders and thus increase profits. The diagnosis begins with the proposal of a research problem. This will help the development of the referential and conceptual framework and the research methodologies to be used, in addition, the general and specific objectives will be studied, the technical, economic, and social justifications and the hypothesis will be disclosed as well. As the main part of the research, we use the selected methodologies for the evaluation and study of different aspects that entail the execution of a project like this. Afterwards, a situational analysis of the company was made in which the process to be improved was defined. We then determined the main root causes through the Ishikawa diagram and the Pareto diagram, this contributed to propose the solution alternatives. Subsequently, the qualitative and quantitative evaluations were a key piece to determine which solution proposals were going to be chosen, this gave way to the development and planning of these. Lastly, we will analyze the economic and financial aspects under indicators such as investment and income and expense budgets, as well as the comparison of indicators before and after the implementation.